2021
DOI: 10.1002/bit.27803
|View full text |Cite
|
Sign up to set email alerts
|

Downstream processing for influenza vaccines and candidates: An update

Abstract: Seasonal and pandemic influenza outbreaks present severe health and economic burdens. To overcome limitations on influenza vaccines' availability and effectiveness, researchers chase universal vaccines providing broad, long-lasting protection against multiple influenza subtypes, and including pandemic ones.Novel influenza vaccine designs are under development, in clinical trials, or reaching the market, namely inactivated, or live-attenuated virus, virus-like particles, or recombinant antigens, searching for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 193 publications
(399 reference statements)
0
10
0
Order By: Relevance
“…As such, the structural integrity of surface antigens on most BGs remains intact [8]. The preparation of inactivated vaccines using methods such as formaldehyde and heat treatments can destroy the surface structures of the bacteria [9,10]. Contrarily, BGs prepared by genetic engineering retain all the structural antigens expressed by pathogenic bacteria, which induces very strong, effective humoral and cellular immune responses [11].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the structural integrity of surface antigens on most BGs remains intact [8]. The preparation of inactivated vaccines using methods such as formaldehyde and heat treatments can destroy the surface structures of the bacteria [9,10]. Contrarily, BGs prepared by genetic engineering retain all the structural antigens expressed by pathogenic bacteria, which induces very strong, effective humoral and cellular immune responses [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we functionalized the base material with unpaired charges to perform separation based on similar principles of anion exchange, one of the most common methods used at large scales to isolate biological particles during bioprocessing. [37,[39][40][41][42][43][44] Despite the increasing application of anion exchange chromatography for EVs and virus-like particles, the recovery of particles from columns is often low. Seo et al recently reported that only 66% of loaded EVs can be recovered from a weak anion exchanger using mild elution buffers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we functionalized the base material with unpaired charges to perform separation based on similar principles of anion exchange, one of the most common methods used at large scales to isolate biological particles during bioprocessing. [ 37,39–44 ]…”
Section: Discussionmentioning
confidence: 99%
“…One of the key challenges in mRNA‐based therapeutics is ensuring the effective delivery of the mRNA to the targeted cells (Brader et al, 2021; Carvalho et al, 2021; Rietwyk & Peer, 2017; Schoenmaker et al, 2021). Although several nonviral delivery systems have been developed, including polymer‐based carriers and inorganic nanoparticles, the greatest success has been achieved with lipid nanoparticles (LNPs) (Hajj & Whitehead, 2017; Mitchell et al, 2021; Pardi et al, 2018; Reichmuth et al, 2016; Tenchov et al, 2021; S. Xu, Yang, et al, 2020; Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The downstream purification process involves a series of chromatographic separations and tangential flow filtration (Jackson et al, 2020;Rosa et al, 2021;Whitley et al, 2022). The purified mRNA is encapsulated in the LNP by mixing the mRNA (in an acidic aqueous buffer) with the lipids (in ethanol) (Carvalho et al, 2021;Nel & Miller, 2021;Reichmuth et al, 2016). The resulting LNP suspension is buffer exchanged and concentrated by ultrafiltration/diafiltration followed by sterile filtration (Rosa et al, 2021) as part of the final fill-finish operation (Moleirinho et al, 2020;van Reis & Zydney, 2007;Zydney, 2021).…”
mentioning
confidence: 99%